The Importance of Considering Information Quality in the Implementation of Service-Oriented Architecture Initiatives - Sulong, Muhammad Suhaizan; Abdul-Aziz, Azlianor; Koronios, Andy; Gao, Jing (2013)
The focus of many organisations shifts towards a new initiative, specifically service-oriented architecture (SOA). The use of SOA enables high-level application integration and the orchestration of business processes in order to realise its full value, including agility and reusability. This shapes the thinking of architects and developers when it comes leveraging computing and information technology (IT) to model, create, operate and manage business processes as services. However, applying SOA initiatives without considering the quality of information makes it impossible for organisations to succeed. Many researchers have looked at the area of information quality (IQ) in terms of the technical aspects of SOA, but there is a gap in the literature when it comes to the process of implementing and deploying an enterprise-wide SOA as a phased, evolutionary process. Thus, this article discusses the importance of IQ throughout the implementation of SOA initiatives. SOA team members from seven case organisations which have been carrying out SOA initiatives were interviewed to gain in-depth insights into IQ in these firms. The results from these various real-world experiences indicate that tying together these two distinctive areas - SOA initiatives and IQ strategy - has a positive effect for a broader audience.